Novel genes and sex differences in COVID-19 severity. Issue 22 (16th June 2022) - Cruz, Raquel; Diz-de Almeida, Silvia; López de Heredia, Miguel; Quintela, Inés; Ceballos, Francisco C; Pita, Guillermo; Lorenzo-Salazar, José M; González-Montelongo, Rafaela; Gago-Domínguez, Manuela; Sevilla Porras, Marta; Tenorio Castaño, Jair Antonio; Nevado, Julian; et al.
Abstract: Here, we describe the results of a genome-wide study conducted in 11 939 coronavirus disease 2019 (COVID-19) positive cases with an extensive clinical information that were recruited from 34 hospitals across Spain (SCOURGE consortium). In sex-disaggregated genome-wide association studies for COVID-19 hospitalization, genome-wide significance ( P < 5 × 10 −8 ) was crossed for variants in 3p21.31 and 21q22.11 loci only among males ( P = 1.3 × 10 −22 and P = 8.1 × 10 −12, respectively), and for variants in 9q21.32 near TLE1 only among females ( P = 4.4 × 10 −8 ). In a second phase, results were combined with an independent Spanish cohort (1598 COVID-19 cases and 1068 population controls), revealing in the overall analysis two novel risk loci in 9p13.3 and 19q13.12, with fine-mapping prioritized variants functionally associated with AQP3 ( P = 2.7 × 10 −8 ) and ARHGAP33 ( P = 1.3 × 10 −8 ), respectively. The meta-analysis of both phases with four European studies stratified by sex from the Host Genetics Initiative (HGI) confirmed the association of the 3p21.31 and 21q22.11 loci predominantly in males and replicated a recently reported variant in 11p13 ( ELF5, P = 4.1 × 10 −8 ). Six of the COVID-19 HGI discovered loci were replicated and an HGI-based genetic risk score predicted the severity strata in SCOURGE. We also found more SNP-heritability and larger heritability differences by age (<60 or ≥60 years) among males than among females. Parallel genome-wide screening of inbreeding depression in SCOURGE also showed an effect of homozygosity in COVID-19 hospitalization and severity and this effect was stronger among older males. In summary, new candidate genes for COVID-19 severity and evidence supporting genetic disparities among sexes are provided.